2016
DOI: 10.5603/gp.2016.0084
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Apa1 (rs7975232), Taq1 (rs731236) and Bsm1 (rs154410) polymorphisms of vitamin D receptor on preterm birth risk in the Polish population

Abstract: Objectives: Vitamin D receptor (VDR) is expressed in the placenta and tissues related to the immune system occurrence of various variants of VDR may modify the effects of vitamin D on pregnancy.The aim of this study was to evaluate the association between the parturients' Apa1, Taq1, and Bsm1 polymorphisms of the VDR and their combinations and the risk of preterm birth in the Polish population. Material and methods:Determination of polymorphism for VDR was assayed using the RT-PCR method. 199 Caucasian women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
16
1
Order By: Relevance
“…A total of 5 studies were from European countries [ 9 , 36 , 38 , 40 , 42 ], 4 from America [ 33 , 35 , 37 , 41 ], and 1 from Asia [ 34 ] and Australia [ 39 ], respectively. Overall, sample sizes ranged from 189 to 615 mothers and from 90 to 506 infants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 5 studies were from European countries [ 9 , 36 , 38 , 40 , 42 ], 4 from America [ 33 , 35 , 37 , 41 ], and 1 from Asia [ 34 ] and Australia [ 39 ], respectively. Overall, sample sizes ranged from 189 to 615 mothers and from 90 to 506 infants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The major risk factors of PTB are certainly maternal age, short inter-pregnancy interval, multiple gestation, drug abuse, smoking, vaginal dysbiosis and infections, low maternal pre-pregnancy weight or inadequate gestational weight gain [ 5 , 6 , 7 , 8 ]. However, the effect of genetic susceptibility has been also well recognized [ 9 ], with novel fetal and maternal genomic variants which in turn affect both intrauterine environment, pregnancy duration and fetal growth [ 10 ]. It has been estimated that approximately 32 million low birth weight (LBW) or small for gestational age (SGA) infants are born annually, with 96.5% of them in developing countries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This SNP was not analyzed in the present study. Similarly, another study involving 199 Polish infants and their mothers identified no association between TaqI, BsmI, and ApaI SNPs on preterm birth (Baczyńska‐Strzecha & Kalinka, ). That study observed that some combinations of alleles significantly reduced the risk of preterm birth, but not the genotypic profile.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, work from a polish group indicates that individual maternal SNPs of the VDR gene, namely the TaqI, BsmI and ApaI polymorphisms, had no effect on preterm birth. But they investigated some genotype combinations and e.g., some combinations reduced the risk for preterm birth significantly [ 174 ]. Polymorphisms of VDR , which are associated with pregnancy complications, are listed in Table 1 .…”
Section: Vdr and Preterm Birthmentioning
confidence: 99%